Perancangan Sistem Inventori Pada CV Bahtera Tuaian Global Dengan Metode Perpetual - Manalu, Soli Vernika; Tukino, Tukino (LPPM Universitas Putera Batam, 2024)
The company's information system currently still utilizes Microsoft Excel in processing inventory quantities. For example, in the process of inputting data on incoming goods, when large quantities of goods come in, a painstaking admin is needed to input the incoming goods. If there is no admin who is diligent in inputting, it is very possible that typos will occur which will result in redundancy or loss of data when inputting incoming goods. Redundancy or loss of data caused by the admin's lack of diligence can result in differences in the amount of inventory in the system and physically. When using applications currently, data cannot be stored centrally in a database, so the risk of data loss caused by admins may occur. Data loss in question is when the admin intentionally or unintentionally deletes data or overwrites data which can result in differences in the amount of inventory. Missing one cell in Microsoft Excel can result in data regarding inventory quantities being incorrect/incorrect.